Effect of essential oil on shelf-life and quality attributes of tomato in Rupandehi, Nepal - Prachand Neupane; Balika Poudel; Binita Wosti; Samikshya Pandey; Mukesh Chaudhary; Ananda G. C.; Ram Prasad Khanal; Jay Chaurasia (Innovations in Agriculture)
Tomato (Lycopersicon esculentum Mill) is one of the most consumed vegetables in the world. Chemicals like Bavistin and Calcium Chloride used to enhance the postharvest life of tomatoes have detrimental effects on human health. An experiment was conducted on tomatoes to determine the effects of essential oils on their physical (color, firmness, weight loss) and chemical attributes (TSS, TA, Vitamin C, pH). Tomatoes were treated with different concentrations of lemon grass oil, calcium chloride (1%), and extract of Justicia adhatoda (100%), and the effects were analyzed along with the control. No significant difference in weight loss was observed among treatments recording maximum weight in Justicia extract treatment (12.86%) and minimum in the control (9.73%). Maximum firmness (5.71 Nmm-1) was recorded in 100% Asuro extract treatment on Day 14 while there was no significant difference in pH on treated tomatoes except on the 10th DAT. A significant difference was noted in TSS, titratable acidity on 4 DAT, and vitamin C content among treatments. TSS content increased up to 10 DAT and showed a gradual diminishing pattern in TSS content in almost all treatments on 12 DAT and 14 DAT where maximum TSS (4.933 Brix) was found in 1% CaCl2 and minimum TSS (3.466 Brix) was found in 200 ppm EO. Furthermore, minimum TA (0.21%) was observed in 200 ppm EO whereas maximum TA was found in tomatoes treated with 100% Asuro extract (0.36) at 14 days after treatment. Additionally, the highest content of Vitamin C (0.276 mgml-1) was recorded in tomatoes treated with 200 ppm of essential oil. There was a significant difference (p < 0.05) in the TSS/TA ratio among treatments during the experiment where the highest ratio (21.08) was observed in 1% CaCl2 and the lowest ratio (9.92) was obtained in 100% Asuro Extract at 14 days after treatment. The current study implies essential oils are potential alternatives to hazardous chemicals enhancing shelf life and safety for human health. It is advisable to carry out multiple experiments in a broader area using different varieties with various concentrations.